STUDI LITERATUR HUBUNGAN FAKTOR RESIKO USIA IBU HAMIL DENGAN ANGKA KEJADIAN PREEKLAMPSIA - Kusumaningtyas, Maria Juliati; Dharmayani, Ni Made Gita Gayatri (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2023)
Preeclampsia is a hypertensive condition accompanied by proteinuria in pregnancies of more than 20 weeks of age, caused by vasospasm and endothelial activation and complicates pregnancy conditions that can cause death in the mother, fetus and neonate. The purpose of this study was to determine the relationship between risk factors for the age of pregnant women and the incidence of preeclampsia. This study used a literature study research method, carried out with data collection activities through literature searches or electronic-based literature reviews using the internet. This study used 25 journals consisting of 17 national journals and 8 international journals. The results showed that there was a relationship between maternal age during pregnancy and the incidence of preeclampsia. and the incidence tends to increase at the age of <20 years and >35 years as a risk factor. So it is necessary to carry out monitoring through adequate and regular Ante Natal Care visits.